Estimating Quality-Affecting Risks in Software Projects - Abdelrafe, E.; Hussin, B. (2011)
Regardless how much effort we make for the success of software projects, many software projects have very high failure rates and risks during their life. In addition to technical risks, the projects normally suffer from risks caused by management practices and conflicts of interests. Risk is not always avoidable, but it is controllable. The aim of this paper is to improve quality of software projects of the participating companies while estimating the quality–affecting risks in IT software projects. The results showed that there were 40 common risks in software projects of IT companies in Palestine. The amount of technical and non-technical difficulties was very large. Our data showed, once again, that most of the risks were very important. The study has been conducted on a group of managers to improve the probability of project success